Innate lymphoid cells are double‐edged swords under the mucosal barrier. Issue 18 (10th August 2021) - Duan, Zhen; Liu, Mandie; Yuan, Lin; Du, Xizi; Wu, Mengping; Yang, Yu; Wang, Leyuan; Zhou, Kai; Yang, Ming; Zou, Yizhou; Xiang, Yang; Qu, Xiangping; et al.
Abstract: As the direct contacting site for pathogens and allergens, the mucosal barrier plays a vital role in the lungs and intestines. Innate lymphoid cells (ILCs) are particularly resident in the mucosal barrier and participate in several pathophysiological processes, such as maintaining or disrupting barrier integrity, preventing various pathogenic invasions. In the pulmonary mucosae, ILCs sometimes aggravate inflammation and mucus hypersecretion but restore airway epithelial integrity and maintain lung tissue homeostasis at other times. In the intestinal mucosae, ILCs can increase epithelial permeability, leading to severe intestinal inflammation on the one hand, and assist mucosal barrier in resisting bacterial invasion on the other hand. In this review, we will illustrate the positive and negative roles of ILCs in mucosal barrier immunity.